Exploring existential interventions that enable competency development in Information Systems students - Rahimi, Saba Ryan (Department of Information Systems, 2015)
The Information Systems field is one characterised by constant debate about its central focus and lack of a defined identity. This debate has perpetuated as the field constantly changes its identity in response to rapid and often turbulent technological advances. By attempting to study humans, computers and the results when humans and computers interact, the field covers a vast intellectual territory. This vastness causes inconsistent focus and different prioritisation across geographic regions, academic institutions and industry entities. In contrast to established fields, where curricula are relatively standardised, Information Systems' curriculum has traditionally been slow to respond to industry needs, generic in nature and has served as a guideline rather than an authoritative truth. This research is concerned with how the nature of the field affects Information Systems students and graduates, and seeks to investigate how learners can contend both the with vastness of the subject matter and the lack of authoritarian guidelines. The theory of existentialism is presented as a possible philosophy that can be instilled in students to help them contend with the nature of the field. Through the gathering of personal accounts from graduates and Graduate Recruitment Officers, this research assesses how students have grown in academia and moved past the challenges of adaptation to industry. In this endeavour it confirms that existential interventions are necessary tools that can be instilled in practitioners to help them contend with the unstable and ever changing nature of the field. In addition, teamwork or the first team experience is determined to be a fundamental event in identity formation. Lastly, significant specialisation change, otherwise called role movement, is identified during this time and could be the subject of further research.